Characterization of avian β-defensin genes in Galliformes reveals widespread evolutionary diversification and distinct evolutionary relationships with infection risk - Xiaoqin Xu; Yi Jian; Lijing Huang; Wei Luo; Bangyuan Wu; Shaohua Feng; Caiquan Zhou; Long Zhang (BMC Genomics, 2025)
Abstract Background Avian β-defensins (AvBDs) represent a key family of antimicrobial host defense peptides in birds. Accumulating evidence suggests that the evolutionary trajectory of β-defensin genes is specific to the gene, timescale, and species involved, implying that species-specific ecological and life-history differences drive divergent selective pressures on these genes. However, their evolutionary dynamics, particularly the interactions with ecological factors and life-history traits, remain insufficiently explored. Results Through a comprehensive survey of 25 species spanning all major clades of Galliformes, 354 AvBD genes were identified. Comparative sequence analysis, genomic organization, and phylogenetic studies collectively reveal significant evolutionary diversification characterized by gene duplication, pseudogenization, and gene loss across these species. Notably, chicken AvBD3 exhibits significant differences in its coding regions, while AvBD6 and AvBD7 appear to have copy number variations, with species-specific paralogs of AvBD6 being especially prominent. Moreover, positive selection was more frequently observed in recently diverged gene lineages compared to ancestral ones. Using 70 samples from eight galliform species, the study further identified the prevalence of species-specific amino acid alleles. Phylogenetic comparative analysis demonstrated that the evolution of nine AvBD genes (AvBD2, -4, -5, -8, -9, -10, -11, -12, and -14) is significantly associated with specific ecological factors and life-history characteristics. Additionally, the evolutionary rates of these genes showed distinct relationship with inferred infection risk, likely reflecting the multifunctionality of β-defensins and potential trade-offs between immune defense and other biological functions. Conclusions This cross-species identification and systematic evolutionary analysis of AvBDs in Galliformes deepen our understanding of the co-evolution of host defense peptides, offering valuable insights into their natural biology and evolution, and paving the way for future applications as alternatives to traditional antibiotics.